Simultaneous Determination of Harmful Aromatic Amine Products of Azo Dyes by Gas Chromatography-Mass Spectrometry - Chormey, Dotse Selali; Zaman, Buse Tugba; Maltepe, Esra; Buyukpinar, Cagdas; Bulgurcuoglu, Ayse Evrim; Turak, Fatma; Erulas, Fatih Ahmet; Bakirdere, Sezgin (PLEIADES PUBLISHING LTD, 2020)
Azo dyes constitute about 66% of all colorants and they are widely used in industries such as textiles, plastics, ceramics, cosmetics and food. However, due to the reductive cleavage of some azo dyes into carcinogenic aromatic amines, many countries have set concentration limits or have banned the use of these azo dyes. Selected aromatic amines that pose health risk to consumers were simultaneously determined by gas chromatography mass spectrometry. A good linearity in calibration plot was obtained for the analytes and the low relative standard deviations indicated high instrumental precision. A recovery test was performed to validate the extraction method and the results obtained were between 92-114%. The method was applied to the analysis of real samples and the concentrations of aromatic amines detected were below the 30 mg/kg limit set by regulatory authorities.
Keywords: azo dyes; aromatic amine; gas chromatography-mass spectrometry; reductive cleavage; Chemistry